Differential Gene and Protein Expressions Responsible for Vasomotor Signaling Provide Mechanistic Bases for the Opposite Flow-Induced Responses of Pre- and Post-Circle of Willis Arteries - Zoltan Nemeth; Krisztian Eros; Gyongyi Munkacsy; Akos Koller (Life)
Increases in flow elicit dilations in the basilar artery (BA) supplied by the posterior cerebral circulation (PCC), and ensuring efficient blood supply to the circle of Willis in which blood flow and pressure can distribute and equalize, and thus provide the appropriate supply for the daughter branches to reach certain brain areas. In contrast, increases in flow elicit constrictions in the middle cerebral artery (MCA), supplied by the anterior cerebral circulation (ACC) and regulating the blood pressure and flow in distal cerebral circulation. Mediators of flow-dependent responses include arachidonic acid (AA) metabolites and nitric oxide (NO). We hypothesized that mediators of flow-dependent responses are differentially expressed in cerebral arteries of the PCC (CAPCC) and ACC (CAACC). The expressions of key enzymes of the AA pathway—cyclooxygenases (COX1/COX2), cytochrome P450 hydroxylases (Cyp450), thromboxane synthase (TXAS), thromboxane A2 (TP) receptor, prostacyclin synthase (PGIS), prostacyclin (IP) receptor (IP); neuronal nitric oxide synthase (nNOS), and endothelial nitric oxide synthase (eNOS)—in the BA and MCA from rats (n = 20) were determined by western blotting. Transcriptome analysis in CAPCC and CAACC from rats (n = 25) was assessed by RNA sequencing. In BA compared to MCA, COX1/2 and Cyp450 protein expressions were lower, PGIS was higher, TXAS and nNOS/eNOS were similar, TP receptors were lower, and IP receptors were higher. Gene expressions of vasodilator canonical pathways were higher in CAPCC; vasoconstriction canonical pathways were higher in CAACC. Mediators of flow-dependent vasomotor signaling are differentially expressed in cerebral arteries of the posterior and anterior circulation, corresponding to their vasomotor function.